FORMULATION AND CHARACTERIZATIONS OF SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEM OF EXTRACT PETIVERIA ALLIACEA (SINGAWALANG) LEAVES - MUSTIKA, ARIFA; FATIMAH, NURMAWATI; SARI, GADIS MEINAR (International Journal of Applied Pharmaceutics, 2019)
Objective: Formulation of Singawalang leaves extract should be considered because the extract contains a variety of compounds so that there may be a competitor in the absorption process and will cause the absorption of active ingredients in the gastrointestinal decline. One way to increase the absorption and disposition of active ingredients on target organs is to use a nanoparticle formulation. Therefore, this study will conduct research on self-nanoemulsifying drug delivery system (SNEDDS) formulation of Singawalang (Petiveria alliacea) leaves extract. Methods: The systems were developed by investigating the solubility Singawalang leaves extract in various carrier oil, the suitable surfactant, and cosurfactant, construction of SNEDDS of Singawalang leaves extract and characterization of droplet size through particle size analyzer and transmission electron microscopy. Results: The results of this study indicate that the optimum carrier oils for Singawalang leave extract are miglitol and virgin coconut oil (VCO), the compatible surfactant component is tween 80 and the compatible cosurfactant is propylene glycol (PG). The average droplet size is 13 nm and polydisperse index 0,004 and 0,006. Conclusion: It can be concluded, the present study demonstrated that the optimum SNEDDS formulations of Singawalang leave extract are the mixture of VCO, tween 80, PG at ratio 1:8:1 and miglitol, tween 80, and PG at ratio 2:5:3.